National Competition for Master's Theses of Pharmaceutical Faculties - Hanna Plata (Polish Pharmaceutical Society, 2020)
In November 2020, the National Competition for Master's Theses of Pharmaceutical Faculties was resolved. It was attended by graduates of pharmaceutical faculties of medical universities from all over Poland, who defended their theses in 2018. The competition was held for the twenty-second time and for the first time in an online formula. Nine best master's theses from medical universities in Białystok, Bydgoszcz, Gdańsk, Katowice, Kraków, Lublin, Poznań, Warsaw, and Wrocław were submitted to the competition. The competition committee chaired by Prof. Dr. Krystyna Olczyk distinguished in a secret ballot the three best works. The first place went to mgr Paulina Wiśniewska from the Medical University of Gdańsk for the thesis "Application of the aza-Michael relationship to the synthesis of new isoxazolone derivatives with potential antibacterial effect", the second place - to mgr Olga Świerzbińska for the thesis "The influence of vitamin K on the regenerative processes of human skin fibroblasts" and third place - mgr Daniel Ziental for the thesis "Phthalocyanines and their potential use in photoinactivation of bacteria".